The Relationship Between Self-Efficacy And Quarter-Life Crisis In Final-Year Students At HKBP University Nommensen Medan - Septia, Gloria; Ambarita, Togi Fitri Afriani (CV Putra Publisher, 2026)
This study aims to analyze the relationship between self-efficacy and quarter-life crisis among final-year students at HKBP Nommensen University, Medan. This study found a significant negative relationship between self-efficacy and quarter-life crisis among final-year students at HKBP Nommensen University, Medan, with a correlation coefficient of -0.358. This finding indicates that the higher a student's self-confidence in their abilities, the lower the level of crisis experienced when facing the transition to early adulthood. The majority of respondents were in the moderate self-efficacy category, with no significant differences between men and women, indicating that gender is not a major determining factor. Although most students have a relatively high level of self-efficacy, many still experience a significant quarter-life crisis. This is influenced by various external challenges, such as social demands, competitive job market, and economic uncertainty. This situation is exacerbated by the lack of a clear plan for post-graduation for some respondents, leading to identity confusion and anxiety about the future. Students with strong self-efficacy are generally more resilient, skilled at solving problems, and adaptable to change, while those with low self-efficacy are more susceptible to stress and obstacles to personal development. These findings suggest the importance of strengthening self-efficacy through self-development programs, career counseling, and social support to help students navigate the challenges of post-graduation life transitions. Therefore, enhancing self-efficacy can be an effective strategy to mitigate the negative impact of the quarter-life crisis on final-year students.